Policy implications of a world with renewables, limited dispatchability, and fixed load - Mathias Mier (University of Oldenburg, Department of Economics, 2018)
Most electricity systems face contractual fixed consumer prices in the short term, that is, load and price are fixed before the random supply of renewables like wind or solar realizes. Steam power plants also make production decisions before such a random supply realizes. These capacities cannot react instantly, which creates a demand for gas turbines to balance renewables. We approach these dynamics by considering different types of dispatchability in a more general framework of peak-load pricing and contribute to the debate on market design and capacity payments. Steam power always recovers costs, gas turbines never do so, and renewables might. We describe possible transfer schemes to overcome this problem and provide a more market-oriented solution. However, consumers must always be compensated for lost load.
Keywords: Q21; Q41; Q42; Q48; L94; L98; 330; renewable energies; peak-load pricing; electricity market design; missing market; missing money; capacity payments